Molecular Epigenetics in the Management of Ovarian Cancer: Are We Investigating a Rational Clinical Promise? - Nguyen, Ha T.; Tian, Geng; Murph, Mandi M. (Frontiers in Oncology, 2014)
Epigenetics is essentially a phenotypical change in gene expression without any alteration of the DNA sequence; the emergence of epigenetics in cancer research and mainstream oncology is fueling new hope. However, it is not yet known whether this knowledge will translate to improved clinical management of ovarian cancer. In this malignancy, women are still undergoing chemotherapy similar to what was approved in 1978, which to this day represents one of the biggest breakthroughs for treating ovarian cancer. While liquid tumors are benefitting from epigenetically-related therapies, solid tumors like ovarian cancer are not (yet?). Herein we will review the science of molecular epigenetics, especially DNA methylation, histone modifications and microRNA, but also include transcription factors since they, too, are important in ovarian cancer. Preclinical and clinical research on the role of epigenetic modifications is summarized as well. Sadly, ovarian cancer remains an idiopathic disease, for the most part, and there are many areas of patient management which could benefit from improved technology. This review will also highlight the evidence suggesting that epigenetics may have preclinical utility in pharmacology and clinical applications for prognosis and diagnosis. Lastly, drugs currently in clinical trials (i.e. histone deacetylase inhibitors) are discussed along with the promise for epigenetics in the exploitation of chemoresistance. Whether epigenetics will ultimately be the answer to better management in ovarian cancer is currently unknown; what we have now is hope.